131 Do siblings of people with multiple sclerosis (MS) have markers of MS risk?. Issue 3 (9th February 2012) - Dobson, R; Meier, U C; Schmierer, K; Giovannoni, G
Abstract : Background: Siblings (sibs) of people with MS (PwMS) have increased risk of MS. As MS risk is multifactorial, it is unclear what contributes to this increased risk. Objectives: To determine if sibs have markers explaining their increased risk. Methods: PwMS (n=38) were recruited along with their asymptomatic sibs (n=51). Healthy controls (HC, n=32) were matched to sibs. MS risk factors were recorded. Serum titres against EBV antigens (EBNA1 and VCA), varicella (VZV), CMV and 25-hydroxyvitaminD (vD) were determined using ELISAs. Results: PwMS were less likely to be male (MS vs sibs p=0.008, MS vs HC p=0.025). There was no difference in month/season of birth and smoking status. PwMS were more likely than HC to have had infectious mononucleosis (p=0.014), there was no significant difference between sibs and HC or PwMS. PwMS had higher anti-EBNA-1 titres than either sibs or HC (MS vs sibs p=0.005, MS vs HC p=0.041). There was no significant difference between groups in anti-VCA, CMV or VZV titres. There was no difference in vD levels between groups. PwMS were more likely to take vD supplements. There was a negative correlation between EDSS and vD (Spearman coefficient 0.338, p=0.041). Conclusions: Sibs of PwMS have characteristics more in common with HC than PwMS. However, results may be clouded by recall bias or the effect of MS on behaviour. More detailed study, including genetic analysis of sibs is required in order to establish determinants of MS risk.